FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN ODHA (ORANG DENGAN HIV/AIDS) DALAM MENJALANI TERAPI ANTIRETROVIRAL DI RSU. Dr. PIRNGADI MEDAN TAHUN 2012 - Linda Maas; Andi ilham (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Antiretroviral therapy was a therapy that taken by people living with HIV/AIDS (PLWHA) to increase their life quality. Although it hasn’t been able to cure disease but antiretroviral therapy could suppress viral load and increase CD4 of PLWHA. More of people living with HIV/AIDS who received ARV, hope their life quality be better if ARV was used obediently. Adherence was a patient's behavior to comply with the provisions given by health workers that include discipline and obedience. To assure adherence, it was critical for patient to receive and understand information about ARV, the ability/ willingness of long-term treatment, the drug-resistance, the side effects, the range of medicines and the time to initiate of therapy. This research aimed to know the associated factors of PLWHA’s adherence at RSU. dr. Pirngadi Medan in 2012. The design of this research was a cross sectional analytic with sample of 59 respondents and obtained by Accidental Sampling. The data analysis were used univariate and bivariate with Chi square test. By the univariate analysis known that respondents had a good knowledge (52.5%), good perception (76.3%), better health services (71.2%). Furthermore social support included in the medium category (57.6%) and adherence of PLHIV was high (57.6%). By the results of bivariate known that there was no associated between knowledge of ARV on adherence (p = 0.648) and there was no associated between perception on adherence (p = 0.231). In addition it was known that there was a associated between social support on adherence (p = 0.047) and there was a associated between health service to the perception patient undergoing ARV (p = 0.040). Health services and all levels of society were expected to continue to provide full support to them so as instill obedience and discipline to patient during undergo treatment and care with antiretroviral therapy.